Magnitude of physiological curvatures of the spine and the incidence of contractures of selected muscle groups in students - Olszewska Elżbieta; Tabor Piotr; Czarniecka Renata (Sciendo, 2018)
Study aim: The aim of this study was to evaluate the incidence of contractures of selected muscle groups with respect to the magnitude of the physiological curvatures of the spine in young men with above-average levels of physical activity.